The essential clathrin adapter protein complex-2 is tumor suppressive specifically in vivo - Seth P. Zimmerman; Lili B. DeGraw; Christopher M. Counter (Nature Communications)
Abstract The microenvironment is a rich source of new cancer targets. We thus used a targeted single-guide RNA library to screen a panel of human pancreatic cancer lines for genes uniquely affecting tumorigenesis. Here we show inactivation of the Adapter Protein complex-2 of clathrin-mediated endocytosis reduces cell growth in vitro, but completely oppositely, promotes tumor growth in vivo. In culture, loss of the complex reduces transferrin endocytosis and iron import required for cell fitness. In tumors, alternative iron transport pathways allow pro-tumor effects of Adapter Protein complex-2 loss to manifest. In the most sensitive case, this is attributed to reprogramming the plasma membrane proteome, retaining integrins on the surface leading to Focal Adhesion Kinase phosphorylation and induction of proliferative signals. Adapter Protein complex-2 function in tumorigenesis is thus dependent upon the microenvironment, behaving as a common essential gene in culture via iron import, but as a tumor suppressor in tumors via integrin trafficking.